Cor triatriatum sinister with left superior vena cava, unroofed coronary syndrome and valvular pulmonary stenosis - Feridoun Sabzi; Aghigh Heydari; Reza Heidari-Moghaddam; Mohammad Rouzbahani; Atefeh Asadmobini (Revista Colombiana de Cardiología, 2022)
A 25-year-old woman with a history of recent dyspnea and palpitation was admitted to our center. Transthoracic echocardiography (TTE) showed an echogenic and septal muscular ridge along the left atrium which were indicative of cor triatriatum sinister (CTS). Further evaluation with transesophageal echocardiography (TEE) showed that a lower chamber of divided left atrium receiving lower right inferior pulmonary vein, mitral valve, left superior vena cava (LSVC) and unroofed coronary sinus (CS). Also, the lower chamber had an unrestrictive communication with the right atrium. The upper accessory chamber receiving one left and one right upper pulmonary vein and communicated with the right atrium by a small atrial septal defect (ASD). However, upper and lower pulmonary venous systems separated directly from each other by a muscular ridge without the presence of any window or hole to allows blood flow between these two accessory chambers. Although the absence of septum associated with the presence of LSVC and unroofed CS makes our case a unique or very rare type of this complex anomaly in an adult case. In our case, surgical removal of dividing muscular membrane with redirection of LSVC and unroofed CS to the right atrium are warranted.